Sürdürülebilir Yönetim Anlayışı Çerçevesinde Gönüllü Karbon Piyasalarında Kullanılan Standartlar ve Bu Standartların Karşılaştırmalı Analizi - SEMİZ ÇELİK, DERYA (My University, 2014)
The studies related with sustainability have been carried out since the first years of the 20th century and it has become a global issue for the last forty years. Climate change, caused by greenhouse gas emissions, is the biggest global threat of the 21st century. As awareness of its impacts grows, many governments and businesses are working hard to reduce their direct CO2 emissions. Voluntary Carbon Market was developed the results of these studies and there are many different standards to certify the green gas emission reductions in this market. The starting point of the voluntary carbon market which is a new concept that has recently entered the literature is a sustainable environment. Within this context in this study sustainability and sustainable management approach has been put forward, the standards that is being used in voluntary carbon market have been analysed and then a comparative analysis of these standards has been made.

Sürdürülebilirlik ile ilgili çalışmalar 20. Yüzyılın ilk senelerinden itibaren yapılmış ve yaklaşık kırk seneden beri küresel olarak ele alınan bir mesele haline gelmiştir. Sera gazı emisyonlarının neden olduğu iklim değişikliği, 21. yüzyılın en büyük küresel tehdididir. Etkileri konusunda farkındalık arttıkça, birçok hükümet ve şirket doğrudan CO2 emisyonlarını azaltmak için çalışmaktadırlar. Gönüllü karbon piyasaları bu tür çalışmaların sonucunda gelişmiştir ve bu piyasada sera gazı azaltımlarını tasdik eden çeşitli standartlar bulunmaktadır. Literatüre son yıllarda giren yeni bir kavram olan gönüllü karbon piyasalarının çıkış noktası sürdürülebilir bir çevredir. Bu çerçevede çalışmamızda sürdürülebilirlik ve sürdürülebilir yönetim anlayışı ortaya konmaya çalışılmış, uluslararası gönüllü karbon standartları irdelenmiş ve ardından da bu standartların karşılaştırmalı analizi yapılmıştır.
A Comparative Analysis of the Standards Used in Voluntary Carbon Markets
Keywords: Sustainability; sustainable management; voluntary carbon markets; standards used in voluntary carbon markets; Sürdürülebilirlik; sürdürülebilir yönetim; gönüllü karbon piyasaları; gönüllü karbon piyasalarında kullanılan standartlar